Tibetan Yoga and Mysticism: A Textual Study of the Yogas of Naropa and Mahamudra Meditation in the Medieval Tradition of Dags po - Timme Kragh, Ulrich (The International Institute for Buddhist Studies, 2015)
A detailed study of a twelfth-century Tibetan corpus of religious writings attributed to the Tibetan master Gampopa Sonam Rinchen (sgam po pa bsod nams rin chen, 1079-1153)